Effects of compost and vermicompost on growth and yield of eggplant Solanum melongena L. - Cantero R., José; Espitia N., Laura; Cardona A., Carlos; Vergara C., César; Araméndiz T., Hermes (Revista de Ciencias Agrícolas, 2015)
Eggplant is conventionally cultivated in the Colombian Caribbean region, with high demand for agricultural inputs. The implementation of ecological crop management is not reported. Facing this problem, the effect of fertilization with organic manures on growth and yield of eggplant Solanum melongena L. crop was evaluated, in the middle valley of the Sinú River, in Córdoba, Colombia. The experiment was conducted in the first semester of 2013 in the experimental area of the Faculty of Agricultural Sciences of the Universidad de Córdoba, with a randomized complete block design, with six treatments: compost, vermicompost, worm-humus leachate, mixture (compost, vermicompost and worm- humus leachate), nitrogen, phosphorus and potassium (NPK) fertilization, and a control (without fertilization) and three replicates. Characteristics regarding days to flowering and harvest, plant height, stem diameter, leaf area, number of fruits per plant, fruit weight, fruit firmness, and yield were evaluated. The analysis of variance showed significant differences in days to flowering, finding that plants fertilized with worm composting were more precocious. No significant differences in days to harvest, plant height, stem diameter, leaf area, number of fruits per plant, fruit weight, and yield were observed. NPK fertilization and compost had the highest minimum rates of marginal return, thus, compost use is a good alternative for sustainable fertilization.